Don't Shoot Yourself in the Foot: Reconstruction of a Through-and-Through Gunshot Wound of the Foot - Brittany Georgia Kay (Plastic and Reconstructive Surgery, Global Open, 2019)
Summary:. A 69-year-old man presented with an accidental, self-inflicted, through-and-through left foot gunshot wound. An entry wound on the dorsum of the foot was noted, with a larger exit wound on the plantar aspect. X-ray revealed comminuted fractures of the second, third, fourth, and fifth metatarsals with numerous foreign bodies. Immediate excisional debridement was performed, and negative-pressure wound therapy was applied. A second look was performed 48 hours later. Five days after initial debridement, a Kirschner wire was utilized for fixation of the second metatarsal fracture, and an external fixator applied to the fifth metatarsal due to extensive bone loss. A free gracilis muscle flap was used to fill the defect, with plans for a vascularized bone graft at a later date. The flap was tunneled through the wound to the plantar aspect of the foot, with an overlying split-thickness skin graft. The patient’s postoperative course was uncomplicated, and secondary bone grafting was not required. The gracilis flap was used to reconstruct the bony and soft tissue defects, and secondary muscle fibrosis appeared to provide adequate skeletal support. The patient was full weight-bearing by 4 months and has since returned to his preoperative activities, baseline gait, and regular footwear. The free gracilis muscle flap may serve as a valuable reconstructive option for through-and-through gunshot wounds to the foot, restoring both contour and function, while eliminating the need for secondary bone grafting.